TLR-Agonist Mediated Enhancement of Antibody-Dependent Effector Functions as Strategy For an HIV-1 Cure - Hvilsom, Caroline Thue; Søgaard, Ole Schmeltz (Frontiers in Immunology, 2021)
Background: The current treatment for HIV-1 is based on blocking various stages in the viral replication cycle using combination antiretroviral therapy (ART). Even though ART effectively controls the infection, it is not curative, and patients must therefore continue treatment life-long. Aim: Here we review recent literature investigating the single or combined effect of toll-like receptor (TLR) agonists and broadly neutralizing antibodies (bNAbs) with the objective to evaluate the evidence for this combination as a means towards an HIV-1 cure. Results: Multiple preclinical studies found significantly enhanced killing of HIV-1 infected cells by by TLR agonists induced innate immune activation or by Fc-mediated effector functions following bNAb administration. However, monotherapy with either agent did not lead to sustained HIV-1 remission in clinical trials among individuals on long-term ART. Notably, findings in non-human primates suggest that a combination of TLR agonists and bNAbs may be able to induce long-term remission after ART cessation and this approach is currently being further investigated in clinical trials. Conclusion: Preclinical findings show beneficial effects of either TLR agonist or bNAb administration for enhancing the elimination of HIV-1 infected cells. Further, TLR agonist-mediated stimulation of innate effector functions in combination with bNAbs may enhance antibody-dependent cellular cytotoxicity and non-human primate studies have shown promising results for this combination strategy. Factors such as immune exhaustion, proviral bNAb sensitivity and time of intervention might impact the clinical success.